Perspectives on the Early Retirement Decisions of Farming Couples - Minna Väre; Almas Heshmati (Institute for the Study of Labor (IZA), 2004)
In the past decade, the European agricultural sector has undergone rapid structural change. Part of that change is manifested in extended early retirement plans. As pensions play a crucial role in determining the characteristics the change, it is important to establish the factors determining the exit from farming among elderly farmers. This study analyses the choice of pension scheme of farmers. The focus is on the effects of farm and off-farm incomes and various offered economic incentives on farmers? retirement decisions. The results provide valuable information concerning evaluation of existing programmes and the design of future retirement systems and policies.
Keywords: C25; Q12; J26; 330; early retirement; farming couple; bivariate probit; Landwirte; Flexible Altersgrenze; Agrareinkommen; Nebenerwerbslandwirtschaft; Privater Transfer; Schätzung; Finnland